Global and National Trends of HIV/AIDS - Raya, Hikmat Bahadur (Nepal Population Journal, 2018)
HIV/AIDS is one of the worst pandemics, the world has ever known and the entire world has been combating with it. Objective of the study is to analyze the global and national trend of HIV/AIDS regarding the indices PLHIV, New infections and AIDS-related death and coverage of ART. This is a quantitative research completely based on the secondary data. The data is analyzed by simple statistical representations. Regression analysis is used to analyze the trends and to make some predictions. The number of PLHIV is increased by 19.9 percent from 1997 to 2015 and by 69.6 percent from 2000 to 2015 in Nepal. In this same duration, the new HIV infection is reduced by 63.8 percent and 82.6 percent, AIDS related death by 52.2 percent and 411.1 percent respectively in the global and Nepal. The initial coverage of ART in both regions was negligible and by the end of 2015 it reached to 46.4 percent and 30.6 percent in the global and Nepal respectively. Nepal along with the global achieves some positive results in the combating of this health problem. By analyzing the trends, it is not worth to say that we are not far from the achievement of SDGs.